Varicella-Zoster Virus and the Enteric Nervous System - Gershon, Michael (J Infect Dis, 2018)
Varicella zoster virus (VZV) infects and becomes latent in sensory, enteric, and other autonomic neurons during the viremia of varicella. Reactivation of VZV in neurons that project to the skin causes the rash of zoster; however, reactivation of VZV in enteric neurons can cause a painful gastrointestinal disorder (“enteric zoster”) without cutaneous manifestations. Detection of VZV DNA in saliva of patients with gastrointestinal symptoms may suggest enteric zoster. This diagnosis is reinforced by observing a response to antiviral therapy and can be confirmed by detecting VZV gene products in intestinal mucosal biopsies. We developed an in vivo guinea pig model that may be useful in studies of VZV latency and reactivation. VZV-infected lymphocytes are used to induce latent infection in sensory and enteric neurons; evidence suggests that exosomes and stimulator of interferon genes (STING) may, by preventing proliferation play roles in the establishment of neuronal latency.